2017
DOI: 10.1186/s12871-017-0380-9
|View full text |Cite
|
Sign up to set email alerts
|

General vs. neuraxial anaesthesia in hip fracture patients: a systematic review and meta-analysis

Abstract: BackgroundHip fracture is a trauma of the elderly. The worldwide number of patients in need of surgery after hip fracture will increase in the coming years. The 30-day mortality ranges between 4 and 14%. Patients’ outcome may be improved by anaesthesia technique (general vs. neuraxial anaesthesia). There is a dearth of evidence from randomised studies regarding to the optimal anaesthesia technique. However, several large non-randomised studies addressing this question have been published from the onset of 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
87
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 37 publications
6
87
3
1
Order By: Relevance
“…However, it is important to note that most of the very elderly patients in our study received regional anaesthesia (76%). This is in line with the general trend of the guidelines and literature [4][5][6][7] requirements for hip joint surgery in elderly patients. Some studies [14,15] suggest that compared with general anaesthesia, regional anaesthesia reduces the incidence of postoperative adverse outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…However, it is important to note that most of the very elderly patients in our study received regional anaesthesia (76%). This is in line with the general trend of the guidelines and literature [4][5][6][7] requirements for hip joint surgery in elderly patients. Some studies [14,15] suggest that compared with general anaesthesia, regional anaesthesia reduces the incidence of postoperative adverse outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…11 In this cohort, fewer patients with COPD received GA, potentially because of co-morbid chest disease altering the riskebenefit judgement about the modality of anaesthesia. In previous studies, little, if any, difference in mortality has been observed between the two modalities 12 ; however, RA has been previously associated with better mortality outcomes specifically in patients with COPD 5 as observed here, although not apparent until 1 yr. This temporal dissociation makes it difficult to attribute the mortality difference directly to the choice of anaesthetic.…”
supporting
confidence: 43%
“…An increased mFI was correlated with an increased mortality rate, which suggests that patient condition worsens as the mFI increases in each follow-up evaluation. Femoral fracture is associated with a substantial risk of mortality and morbidity with approximately 1%-6% of patients dying within 30 days of admission (10,11). In this study, the hospital mortality rate was 3.8%, and the 30-day mortality rate was 9.8%.…”
Section: Discussionmentioning
confidence: 67%
“…Frailty is a known independent factor associated with postoperative mortality and morbidity as well as the length of hospital stay and has been shown to increase the risk of mortality. Patients with femoral fracture represent an elderly group with varied levels of frailty (10)(11)(12). In our patient population, 127 (27.6%) had mFI≥7.…”
Section: Discussionmentioning
confidence: 99%